Theoretical investigation into exhaust gas energetic utilisation - Török, Ádám; Stubán, Norbert (Transport, 2010)
Sustainable development is a kind of development where the pace of technical development, the satiation of increasing supply and the raw materials and resources of the Earth are poised so that the rate of living and the opportunities of the future generations should not decline. For this reason, transportation systems must be developed and the effectiveness of transportation service must be increased while environmental pollution must be decreased or prevented. Vehicles are burning fuels inefficiently. There are two options of decreasing environmental impacts – one is to reduce fuel consumption while another is to do it in a more acceptable way increasing efficiency. There is justifiable demand put forward by the society to moderate environmental impacts caused by road transportation. This article deals with modelling the energetic utilisation of exhaust gas. First published online: 10 Feb 2011